La desprotección jurídica de sujetos de atención prioritaria en cuanto a la aplicación de medidas cautelares personales. propuesta de reforma al art. 171 del código de procedimiento penal. - Pachar Vivanco, Tito Max (2011)
The present thesis refers to the complex one problematic social, politics and artificial that is generated as consequence of the affection of fundamental and specific laws of those subject of high-priority attention foreseen in Art. 35 of the Ecuador’s Republic’s Constitution this belongs to mature biggest people, girls, children and adolescents, pregnant women, people with inability, patient of catastrophic illnesses and of high complexity and all person that it is in situation of risk who are discriminated against with regard to the possibility of application of alternative precautionary measures to the preventive prison, when in Art. 171 of the Code of Penal Procedure, it is determined that in the case of crimes against the public administration, of that can results the death of one or more people, of sexual crimes, of hate, of those sanctioned with reclusion hardships, or when the repetition circumstance converges, the substitution of the preventive prison won't be accepted, not even for the domiciliary arrest, in this case evidently affects the essential laws to the equality in front of the law of those people, all time that the related dispositions of the Code of Penal Procedure, allow the substitution of the preventive prison for alternative exclusive measures of freedom to the judge's discretion or judge of penal guarantees, considering the circumstances characteristic of the offender's act above all, the criminal's personality, the danger and their necessities as regards rehabilitation, this of conformity with Art. 77, numeral 11, of. Ecuador’s Republic Constitution. The present research held to the academic requirements of the National University of Loja, it begins firstly with a general summary of the work, to the same one that I have translated it to the English language; subsequently I present the introduction that offers some general ideas on the studied problem and the outlined contents. Then I present the literature revision that begins with the elaboration of a conceptual mark whose contents are the scientific definition of the juridical categories that they converge in this thesis, like it is the case of the human laws, of the penal process, of the precautionary measures, of their classification and socio-political ends, of the groups of high-priority attention and of the preventive prison. Then I indicate the doctrinal mark that approaches the study of the human laws and I contrast them with the reality procedural prison of those subject of high-priority attention, I also study the due process and the preventive prison, I conclude with the study of the limits that impose the fundamental laws from people to the preventive prison. The literature revision is supplemented with the development of the juridical mark; next, I analyze in itemized form what concerns to the precautionary measures in the place of Penal Procedure Code; I also carry out, I do a analysis juridical critic of the Art. 171 in this mentioned Code. Later I have proceeded to describe the materials and used methods; the presentation of the results of surveys and applied interviews, and the study of cases. On the base of this result, I have been able to verify the objectives and to contrast the hypothesis, and to base the proposal of legal reformation. Lastly I have outlined the conclusions, recommendations and the Project of Reformation to Art. 171 of the Code of Penal Procedure